Consumer preferences in wine: traditional vs fungus-resistant varieties in Switzerland - Marie Blackford; Barbara Guggenbühl-Gasser; Jonas Inderbitzin; Martin Wiederkehr; Pascal Fuchsmann; Stefan Bieri; Kathleen Mackie-Haas (OENO One)
A growing interest in sustainable viticulture has led to the development of fungus-resistant grape (FRG) varieties, but their acceptance by consumers remains uncertain. This study explores Swiss consumers’ perceptions of wines made from FRG varieties compared to traditional grape varieties. Specifically, it investigates (i) potential differences in consumer acceptance of FRG wines and traditional wines, (ii) segmentation of consumers based on their appreciation of FRG wines, and (iii) the influence of information about FRG on consumer perception. To address these questions, we conducted a multi-phase study combining chemical wine analysis, expert sensory profiling and consumer blind tastings of FRG wines and traditional and commercial wines in three cities across Switzerland (Nyon (Vaud), Liebefeld (Bern) and Wädenswil (Zurich)). Half of the participants were informed that they were tasting wines made from FRG varieties, while the other half were not. The results indicate that FRG wines are, on average, as appreciated as traditional varieties. Furthermore, consumers can be segmented into three distinct preference groups. This study identifies three key drivers of consumer acceptance: organoleptic attributes, wine-knowledge of the targeted consumer cluster and prior awareness of FRG. While additional information on the environmental benefits of FRG wines did not influence overall consumer appreciation, one cluster of consumers was affected by the information provided. These findings have important implications for winegrowers, suggesting that marketing strategies should be tailored to different consumer segments, emphasising sensory qualities while strategically using information disclosure.